The Effectiveness of an Educational Intervention Based on Teach-back Method with Adherence to Treatment in Patients with Type 2 Diabetes - Saeed Hosseini Teshnizi; Samiyeh Sadeghpour; Aref Faghih (Shiraz University of Medical Sciences, 2024)
Background: Patients' adherence to the therapeutic regimen predicts the success of treatment and reduces the complications and severity of the disease. The purpose of this study was to determine the effectiveness of an educational intervention based on Teach-back method with adherence to treatment in patients with type 2 diabetes.Methods: We performed a quasi-experimental study on 90 patients with type 2 diabetes in the control and experimental groups. Data collection tools were a two-part questionnaire which consisted of the demographic information and the Mandaloo treatment adherence questionnaire with 40 questions. An educational intervention was performed for the members of the intervention group. One week and forty days after the intervention, the two groups filled out the treatment adherence questionnaire again. The gathered data were analyzed in SPSS software version 22 using statistical tests of Wilcoxon, Chisquare, Makhli, Ben Foroni, the repeated-measures variance of analysis, and independent t-test. The significance level in this study was considered less than 0.05.Results: The mean scores of adherence to treatment in the training group before the intervention, one week, and forty days after the intervention were 120.52±11.49, 157.60±17.96, and 140.65±18.80, respectively; also, in the control group, the mean scores were 113.38±16.89, 150.67±18.58, and 145.02±18. 47, respectively. There was no difference in terms of adherence to treatment between the control and experiment groups (P=0.164).Conclusion: The findings also showed that adherence to treatment in both groups in all three measurement times was at the fitness level.